2021
DOI: 10.1186/s42490-021-00048-6
|View full text |Cite
|
Sign up to set email alerts
|

Approaches in cooling of resistive coil-based low-field Magnetic Resonance Imaging (MRI) systems for application in low resource settings

Abstract: Magnetic Resonance Imaging (MRI), a non-invasive method for the diagnosis of diverse health conditions has experienced growing popularity over other imaging modalities like ultrasound and Computer Tomography. Initially, proof-of-concept and earlier MRI systems were based on resistive and permanent magnet technology. However, superconducting magnets have long held monopoly of the market for MRI systems with their high-field (HF) strength capability, although they present high construction, installation, and sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Ogbole et al noted that lack of technical support or service materials caused significant scanner downtime 51 . When designing devices for LMICs, special consideration should be given to available resources and expertise 54,55 . Additionally, many LMICs have a dearth of radiologists and radiographers 56 .…”
Section: Financial and Practical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ogbole et al noted that lack of technical support or service materials caused significant scanner downtime 51 . When designing devices for LMICs, special consideration should be given to available resources and expertise 54,55 . Additionally, many LMICs have a dearth of radiologists and radiographers 56 .…”
Section: Financial and Practical Considerationsmentioning
confidence: 99%
“…51 When designing devices for LMICs, special consideration should be given to available resources and expertise. 54,55 Additionally, many LMICs have a dearth of radiologists and radiographers. 56 Remote readers or automated algorithms may provide diagnostic support, allowing countries to stretch scarce resources.…”
Section: Financial and Practical Considerationsmentioning
confidence: 99%
“…Computing (and optimising) the magnetic fields of single coil arrangements is not trivial, but the equations are well described [38]. The generation of field gradients via electromagnets (superconductor, but also resistive coil based) is well known for magnetic resonance imaging (MRI) [39]. Of special interest for LGMS in tubular or elongated geometries are horizontal coil arrangements used to control the vertical field gradient in MRI scanners, such as Golay coils (see Figure 2b) [40].…”
Section: Electromagnetic Separator Designsmentioning
confidence: 99%
“…m [g/s] is the mass flow rate of solution through the separator, c p [J/K] is the solution's specific heat capacity (here water was assumed), and ∆T [K] is the temperature difference between the separator inlet and outlet. Although Equation (15) overestimates the temperature increase, as it neglects cooling at the tubing wall (or possible cooling in the wire [39]), it was used as an additional constraint, i.e., ∆T should not exceed 10 • C. As low flow rates caused the solutions to heat up, the separation efficiency had to be compromised to meet the new constraint. The same iterative approach as described above was used to find the highest SE with the additional temperature constraint.…”
Section: Optimum Separation Conditions For 250 Nm Mnpsmentioning
confidence: 99%
“…Moreover, Hömmen et al [10] revealed that existing ultra low-eld MRI systems can produce a su cient signal-to-noise ratio (SNR) required for clinical imaging. Huang et al [11] revealed that portable low-cost MRI systems can provide a point of care and timely MRI diagnosis especially to low-income countries where there are less than 0.1 MRI scans per 1,000,000 people [12] [13]. Several studies [8], [14] have indicated that low-eld MRI scanners have a low signal-to-noise ratio (SNR), resulting in noisy images.…”
Section: Introductionmentioning
confidence: 99%